An Application for Smartphones and Computers to Diagnose and Control Potatoes Insects - Zaeen, Ahmed Asaad; Dhedan, Ruaa Muhammed; Sharma, Lakesh K. (Iraqi Journal of Science, 2023)
Nowadays, a strong relationship between the agriculture sectors and digital technologies is really interesting. The article describes how recent intelligent technologies can improve agricultural fields. Mobile applications are software programs created on smartphones, tablets, and computers. Agricultural fields mainly represent the pillar of the economy and the business sector that fulfills the world's food requirements. The United States has a valuable rank in potato production, which depends on this production economically.Nevertheless, so many insects affect potato yield production quantitatively and qualitatively. So, a smartphone App was created to help potato growers diagnose insects that directly attack potato crops and treat them. The created App focuses on a list of the common insects that attack potato crops in Maine State. App Inventor Platform, run by the Massachusetts Institute of Technology (MIT), was used to develop the application. Insect images and insecticides information were collected from the Cooperative Extension Department at Presque Isle City, Aroostook County, Maine, USA. The App provides essential details regarding insect types, life cycles, where they are coming from, and the time of attacking the plants. The App includes a list of effective insecticides that control insects. The App also provides helpful instructions concerning trade names, dose per acre of insecticides, and whether it should be applied to soil or plant leaves. Money and time are saved by applying this App since farmers do not need to spend time collecting samples and bringing them to the lab.